The Hypothesis of the Relationship Between the Current Seismic Process and the Geomagnetic Field Pulsations - Brodsky, Yu.B.; Gannoshyn, V.P. (Український антарктичний журнал, 2009)
With respect to the increased frequency of the seismic activity symptoms and their disastrous aftereffects and taking into account the publications devoted to severe earthquakes in the Antarctics (1998), Kaliningrad oblast (2004), China (2008), Kirghizia (2008), South Pakistan (2008) and other places, the paper presents the analysis of the influence of the seismic process on the effects in the circumterrestrial plasma. The authors propose a new hypothesis of the relationship in the lithosphere – geomagnetic field system which is based on the interaction between the moving tectonic plates and the Earth's magnetic field. В связи с участившимися случаями проявления сейсмической активности и их катастрофическими последствиями, с учетом опубликованных материалов о сильных землетрясениях в Антарктиде (1998 год), Калининградской области (2004 год), Китае (2008 год), Киргизии (2008 год), Южном Пакистане (2008 год) и многих других представлен анализ влияния сейсмического процесса на эффекты в околоземной плазме. Предложена новая гипотеза связи в системе литосфера–геомагнитное поле, основанная на взаимодействии движущихся тектонических плит с магнитным полем Земли.